Digital Marketing: Shredded Toman Fish and Forest Honey Products of Lati Petangis Forest Park - Surahman Surahman; M. Kiswanto; Yuan Regiyana; Nuria Hayati; Afvira Ramahdany; Rif’ah Rif’ah; Patimah Patimah (Universitas Muhammadiyah Magelang, 2021)
abstract